The role of theoretical debate in the evolution of national and international patent protection : from the French Revolution to the Paris Convention of 1883 - Duncan, Louise J. (Legal History Library / Studies in the History of International Law, 2021)
This volume offers a detailed account of the development of national patent systems, and then moving on to the international sphere to discuss the factors which provided the impetus for the Paris Convention for the Protection of Industrial Property (1883).